Vascular Effects of Eplerenone in Coronary Artery Disease With Preserved Ejection Fraction: A Double‐Blind, Randomized, Placebo‐Controlled Trial - Sudano, Isabella (Clin Cardiol, 2016)
BACKGROUND: Mineralocorticoid receptor antagonists (MRAs) reduce morbidity and mortality in heart failure with reduced ejection fraction (HFrEF). Their role in patients without heart failure, particularly in patients with coronary artery disease (CAD) and preserved EF, is still a matter of debate. HYPOTHESIS: The MRA eplerenone on top of standard medical therapy improves endothelial dysfunction and other markers of vascular health in CAD patients with preserved EF. METHODS: In this double‐blind, randomized, placebo‐controlled study, 42 patients (mean age: 63.5 ± 9.1 years; 37 males) were randomized to 4‐week treatment with eplerenone 25 mg daily or placebo. The primary endpoint was difference in endothelial function as assessed by flow‐mediated dilatation (FMD) of the brachial artery. Secondary endpoints included 24‐hour blood pressure (BP), endothelial progenitor cells, and platelet adhesion. RESULTS: No difference in the primary endpoint FMD was noted after 4 weeks of treatment with eplerenone compared with placebo (FMD: 4.7% ± 2.0% and 4.9% ± 2.1%, respectively; P = 0.77). There were no significant differences between eplerenone and placebo in 24‐hour BP (mean systolic BP: 126.9 ± 17.3 and 123.3 ± 9.7 mm Hg, P = 0.41; diastolic BP: 73.3 ± 12.9 and 72.0 ± 7.5 mm Hg, respectively, P = 0.69), number of endothelial progenitor cells, and platelet adhesion. CONCLUSIONS: Adding low‐dose eplerenone to standard medical therapy did not improve important markers of vascular health in patients with CAD and preserved EF. Our results may help understand conflicting evidence from larger clinical trials on MRAs in patients with preserved EF.